TEKNIK SUPERVISI DALAM PENDIDIKAN ISLAM - Andita Dwi Puspita Ningsih; Ahmad Manshur (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2025)
Islamic educational supervision is a systematic effort to guide and enhance the professional quality of teachers based on Islamic spiritual and moral values. This study aims to describe the concepts, techniques, and challenges in the implementation of supervision within Islamic education. The research employs a descriptive qualitative approach through literature analysis that integrates modern supervision theories with Islamic educational principles. The results indicate that supervision in the Islamic context is not merely a form of control but a process of guidance and mentorship (taujih and tarbiyah) emphasizing the values of amar ma’ruf nahi munkar, sincerity, and moral responsibility. Supervision techniques can be conducted individually or in groups, such as classroom observation, interviews, workshops, and peer supervision. However, its implementation still faces several challenges, including limited supervisor competence, control-oriented paradigms, and low teacher awareness of the importance of Islamic-based supervision. Therefore, continuous strategies are needed, such as capacity building for supervisors, collaborative approaches, and the use of supervision instruments aligned with Islamic values. Supervision grounded in Islamic principles is expected to develop educators who are professional, morally upright, and committed to improving the overall quality of education sustainably